Probing batch and continuous flow reactions in organic solvents: Granulicella tundricola hydroxynitrile lyase (GtHNL). Issue 11 (21st May 2020) - Coloma, José; Guiavarc'h, Yann; Hagedoorn, Peter-Leon; Hanefeld, Ulf
Abstract : Granulicella tundricola hydroxynitrile lyase ( Gt HNL) is a manganese dependent cupin which catalyses the enantioselective synthesis of ( R )-cyanohydrins. Abstract : Granulicella tundricola hydroxynitrile lyase ( Gt HNL) is a manganese dependent cupin which catalyses the enantioselective synthesis of ( R )-cyanohydrins. The Gt HNL triple variant A40H/V42T/Q110H, previously reported to exhibit a high activity and stability, was immobilised on Celite R-633 by adsorption. The synthesis of ( R )-mandelonitrile catalysed by immobilised enzyme in a rotating bed reactor was compared to a continuous flow reactor. A batch reaction was used as reference system and organic solvent (MTBE) was used as reaction medium to suppress the chemical background reaction, ensuring the synthesis of enantiopure cyanohydrin. The rotating bed reactor, designed to boost conversion rates due to enhanced mass transfer, did not greatly enhance the reaction displaying a rate 1.7 times higher than the reference batch model. Moreover, similar conversion (96% after 4 hours) and recyclability were observed as compared to the reference system. The continuous flow reactor displayed rates 2 and 3 times higher than the rotating bed and the reference batch systems, respectively. Good conversions were achieved within minutes (97% conversion in 4 minutes at 0.1 mL min −1 ). The immobilised enzyme displayed excellent enantioselectivity and high operational stability under all evaluated conditions. Overall, Gt HNL triple variant A40H/V42T/Q110H immobilised on Celite R-633 is an excellent catalyst for the synthesis of ( R )-mandelonitrile with a great potential for continuous flow production of cyanohydrins.